Circular Migration and Triple Benefits: The Case of Albanian Migrants to Italy - Kodra, Mejola (Mediterranean Journal of Social Sciences, 2021)
According to the 2008 IOM Report on Migration in the World, circular migration is "the fluid movement of people between countries, including temporary or long-term movements, which can be beneficial to all entities involved, if it happens voluntarily and if it is related to the labor market needs of the countries of origin and destination.â€ The already 30-year experience of emigration of Albanians to Italy has shaped new models of migration. The historical migration between the two countries, as well as the long migratory experience after the fall of the communist regime, has enabled the circulation of many individuals between the two countries.The purpose of this study is to explore through the experiences of migrants moving between Albania and Italy, their contribution to themselves, as well as for the host country and that of origin. This paper is based on a combination of data obtained from secondary sources, such as: studies and research by foreign and Albanian authors, reports and literature focused mainly on circular migrants, but not only, as well as primary data obtained from direct interviews and focus groups with 15 circular migrants. Based on the perceptions generated by the migrants themselves, who participated in this study, there seems to be a threefold benefit from this migration process, despite the fact that migrants' perceptions take on different nuances in relation to these benefits that sometimes lean more towards themselves, sometimes from the host country and sometimes from the country of origin. Throughout the interviews it was noted that migrants did not know policies in support of this category, either from the host country or from the country of origin, which can be considered as an important step to be taken in the framework of interstate cooperation, to increase the triple benefit from this type of migration. Â  Received: 5 May 2021 / Accepted: 14 June 2021 / Published: 8 July 2021